Demographic change and the rate of return in pay-as-you-go pension systems - Matthias Schön (Journal of Population Economics, 2023)
The ongoing demographic change in most developed countries consists of two coinciding independent developments that differ in structure and persistence: A slow, monotonic and (presumably) permanent longevity effect caused by an increasing life expectancy; and a more rapidly changing, non-monotonic and less permanent cohort effect caused by fluctuations in the size of cohorts. This paper shows the longevity effect has a positive impact on the rates of return households generate within a pay-as-you-go (PAYG) pension system. The cohort effect, by contrast, results in winners and losers in PAYG systems. The paper additionally shows that the type of PAYG pension system alters the results significantly. Taking the remarkable demographic change in Germany as an example, a large-scale overlapping generation model quantifies rates of return within the PAYG pension system for every cohort. The results show that the two effects combined cause return differentials of almost 1.3 percentage points between generations.
Keywords: 330; Demographic change; Pension system; OLG models